Automatic pressure control system - Koreisová, Gabriela; Koreis, Josef (Univerzita Pardubice, 2008)
The article describes static dynamic properties of the pressure control system in an opened hydraulic circuit with a regulating hydra ulic generator. First, simulation models are assembled of static and dynamic properties of the pressure control unit and controlling servo-cylinder of the hydra ulic generator. Subsequently, a simulation model is assembled of the static and dynamic properties of the entire automatic pressure control system.
Systém automatického řízení tlaku
Automatisches Drucksteureung System